272 Engaging Michigan’s Rural, Upper Peninsula Community in Translational Science to Advance Community Engagement Among Nonprofits - Karen Calhoun; Tricia Piechowski; David Cordova; Barbara Israel; Sarah Bailey; Polly Y. Gipson Allen (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: The Michigan Institute for Clinical & Health Research (MICHR) Community Engagement (CE) Program fosters translational science and community-engaged research (CenR) through education, connecting, supporting, and funding efforts and opportunities. METHODS/STUDY POPULATION: In Michigan’s Upper Peninsula, CE partnered with the Michigan Health Endowment Fund to develop a 3-hour workshop that consisted of a panel discussion on best practices of community engagement and a presentation on community engaged nonprofit management. The workshop was designed from mapping 60 participants’ pre-workshop survey findings and reviewing themes from a planning meeting transcript with six community partners. Key themes that emerged included participatory budgeting, collaborative governance, communications, and community planning. RESULTS/ANTICIPATED RESULTS: A mix methods post-workshop evaluation feedback survey was completed. The 9-item survey assessed workshop content, satisfaction, and knowledge gained using a Likert scale as well as opened questions about key takeaway and value added. Quantitative results to be analyzed. Qualitatively, some participants described the workshop as helpful and thoughtful about how to strengthen community engagement within their organizations. Others expressed a desire for more time. Regarding impact, CE received an uptake in consultations and inquiries into statewide pilot grants. The workshop facilitated new collaborations with philanthropic and community organizations serving the Upper Peninsula. DISCUSSION/SIGNIFICANCE: Lessons learned highlight trust, understanding community culture, and moving slowly in a newly formed collaboration. The approach utilized in the Upper Peninsula can inform translational methods for additional partnerships underway across the state of Michigan.